2015
DOI: 10.1007/s10592-015-0711-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Galium cracoviense (Rubiaceae): a naturally rare species with an extremely small distribution range

Abstract: Galium cracoviense is a narrow endemic diploid species with a highly restricted natural range of occurrence, confined to a system of limestone outcrops in an area covering ca. 25 km 2 in southern Poland. It is an excellent example of a naturally very rare species which most probably has persisted in the same area since its divergence. We used the first exhaustive inventory of its subpopulations, range-wide fine-scale sampling and AFLP fingerprinting to examine the genetic structure of G. cracoviense. The aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…This pattern of distribution agrees with that expected in a scenario characterised by limited seed dispersal (Cieślak et al . ). In addition, we also found that pollinators move over short distances.…”
Section: Discussionmentioning
confidence: 97%
“…This pattern of distribution agrees with that expected in a scenario characterised by limited seed dispersal (Cieślak et al . ). In addition, we also found that pollinators move over short distances.…”
Section: Discussionmentioning
confidence: 97%
“…Endemic species are plants that occur in specific habitats and are geographically restricted, but such plants can be sparse or abundant, meaning that they can have different population sizes and spatial arrangements ( Rabinowitz, 1981 ). A common assumption is that endemic species are rare and genetically depleted, presenting low genetic diversity and strong population differentiation ( Binks et al , 2015 ; Ciéslak et al , 2015 ). However, many examples can be found in the literature that contradict this statement ( Hou and Lou, 2011 ; Ciéslak et al , 2015 ; Turchetto et al , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A common assumption is that endemic species are rare and genetically depleted, presenting low genetic diversity and strong population differentiation ( Binks et al , 2015 ; Ciéslak et al , 2015 ). However, many examples can be found in the literature that contradict this statement ( Hou and Lou, 2011 ; Ciéslak et al , 2015 ; Turchetto et al , 2016 ). Absent or limited gene flow and inbreeding are putative drivers for the genetic diversity pattern associated with small or restricted population sizes ( Ellstrand and Elam, 1993 ), and several other factors can influence the genetic diversity and population structure of rare species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Šmídová et al, 2011) or Pedicularis sudetica Willd. (Hendrych and Hendrychová, 1988), became glacial or postglacial relicts, but also new local endemics appeared, e.g., Galium sudeticum Tausch, G. cracoviense Ehrend., Cochlearia polonica E. Froelich (Cieślak et al, 2007(Cieślak et al, , 2015Szeląg, 2009, 2010;Kolář et al, 2013Kolář et al, , 2015 or Sorbus sudetica (Tausch) Bluff et al (Kaplan, 2012). Climatic changes during the Quaternary Period strongly affected the species composition and the species distribution in Europe (Szafer, 1946(Szafer, -47, 1954Kaplan, 2012).…”
Section: Introductionmentioning
confidence: 99%